2021
DOI: 10.1186/s12880-021-00678-1
|View full text |Cite
|
Sign up to set email alerts
|

Developing a model for estimating infarction onset time based on computed tomography radiomics in patients with acute middle cerebral artery occlusion

Abstract: Background Radiomics analysis is a newly emerging quantitative image analysis technique. The aim of this study was to extract a radiomics signature from the computed tomography (CT) imaging to determine the infarction onset time in patients with acute middle cerebral artery occlusion (MCAO). Methods A total of 123 patients with acute MCAO in the M1 segment (85 patients in the development cohort and 38 patients in the validation cohort) were enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…Wen et al also developed a CT-based radiomics model to predict infarct onset time in patients with MCAO. They obtained similar results with the combined model (AUC of 0.808-0.833) [60]. Finally, Zhang et al also developed an MRI-based radiomics model to predict TSS with similar results [61].…”
Section: Time Since Stroke Predictionmentioning
confidence: 69%
“…Wen et al also developed a CT-based radiomics model to predict infarct onset time in patients with MCAO. They obtained similar results with the combined model (AUC of 0.808-0.833) [60]. Finally, Zhang et al also developed an MRI-based radiomics model to predict TSS with similar results [61].…”
Section: Time Since Stroke Predictionmentioning
confidence: 69%
“…27 When considering the diagnosis of stroke at an early stage, evidence supports the benefits of intravenous tissue plasminogen activator administration within 4.5 hours after symptom onset in ischemic stroke patients. 28 Wen and colleagues 29 leveraged this knowledge to extract radiomic features from CT images to determine the infarction onset time in patients with acute middle cerebral artery occlusion. They concluded that radiomic features were able to guide thrombolytic therapy in patients with uncertain stroke onset time.…”
Section: Early Detectionmentioning
confidence: 99%
“…Metal artifacts are image abnormalities caused by metal substances in the patient’s body that may obscure important anatomical structures or areas of the lesion. In MRI imaging, metal artifacts may reduce the clarity of brain structures and interfere with the doctor’s diagnosis [ 17 ]. Additionally, the selection of imaging parameters will directly affect the image quality.…”
Section: High Frame Rate Imaging Algorithmmentioning
confidence: 99%